Radio, mobility and ubiquity : analysis of Abert’s mobile digital inclusion project. - Bianco, Nelia Rodrigues Del (2018)
Mobile phones have become the main device for consuming radio content, broadening the traditional forms of mobility once restricted to transistor radios and automobiles. In an effort to have small and medium-sized radio stations incorporate the use of digital mobile phones, the Associação Brasileira de Emissoras de Rádio e TV has created a project called Mobilize-se. This project provides a free radio integration app; a radio app exclusive to smartphones; and a social network page. There are about 700 radio stations currently participating in this project. The goal of this quantitative/ qualitative study was to understand how these radio stations have benefitted from the advantages of digital inclusion (FLICK, 2009; CODINA et al, 2011) by using data triangulation (MINAYO; ASSIS; SOUZA, 2005) to assess the impact that digital inclusion has had on them. The results indicate that broadcasters have made this inclusion without too much forethought, and are not fully caught up with marketing strategies.